Scroll compressor. Analysis of calculation methods - Kovanov, A.V.; Zhignovskaya, D.V.; Tsvetkov, V.A.; Pronin, V.A. (Recent Contributions to Physics, 2021)
The paper deals with some aspects of mathematical modeling of a scroll compressor. Various approaches to modeling the working processes of machines of the volumetric compression principle, their applied value and priority of use are presented. An analytical review of the methods for calculating the leakage of a compressed medium, applied to a scroll compressor, taking into account the classification of slots, is carried out. Conclusions are made about the need to clarify the assumptions and improve this technique by taking into account the fact of the mobility of the walls of the gap, depending on the share of the influence of various factors on the leakage of the compressed medium. And also about the influence of this fact on the accuracy of calculations and the optimal choice of the operating mode of the compressor. Examples are given in which taking this condition into account in the transformed systems of equations will improve the accuracy in applied calculations of the working processes of spiral machines, when designing new samples.